Freezing/festination during motor tasks in early‐stage Parkinson's disease: A prospective study. Issue 12 (13th September 2016) - Delval, Arnaud; Rambour, Mélanie; Tard, Céline; Dujardin, Kathy; Devos, David; Bleuse, Séverine; Defebvre, Luc; Moreau, Caroline
ABSTRACT: Background: Parkinsonian patients have a tendency to speed up during repetitive motor tasks (festination) and to experience sudden motor blocks (freezing). In this article, we prospectively studied the appearance and progression of these phenomena in 30 early‐stage PD patients. Methods: A total of 30 controls and early‐stage PD patients were assessed in the "off‐drug" condition at baseline and 2 years later. Freezing of gait was evaluated using a standardized gait trajectory with the usual triggers. Patients also performed diadochokinetic tasks with 3 different effectors (repetitive, antiphase movements for the hands and feet, and repetitive syllable production for the orofacial effector) at frequencies ranging from 1 to 7 Hz (in random order). The primary endpoint was the occurrence of freezing and festination. Results: At baseline, freezing was observed in 6.5% of the trials in PD patients (43% of the patients) and 2.3% of the trials in controls, and festination was observed in 5.7% of the trials in patients (53% of the patients) and 0.8% of the trials in controls. These proportions were slightly higher in patients 2 years later. None of the patients presented freezing of gait at baseline, but 2 displayed this condition 2 years later. These phenomena occurred more frequently for the limb effectors than for the orofacial effector. Freezing and festination were associated with the akinetic‐rigid subtype, although tremor‐dominant patients displayed greater rhythm variability outside episodes. Conclusion: Freezing and festination of the upper and lower limbs are observed soon after the diagnosis of PD and may be early biomarkers for disease progression. © 2016 International Parkinson and Movement Disorder Society